Tecnologia, educação e trabalho: percepções e desdobramentos oriundos do Ensino Remoto Emergencial-ERE no interior da Amazônia - Sousa, Benara Modesto de (2023)
This research addressed Emergency Remote Teaching from a laboratory perspective, understanding the role of teaching and learning methodologies and educational technologies in this process of re-signification of education, specifically in Professional and Technological Education Technical Middle Level - PTETML, starting from critical theoretical bases and discussing the inseparable relationship between work, technology and education. The research adheres to the research line: Organization and memories of Pedagogical Spaces in Professional and Technological Education. Nucleating in the macroproject: Organization of the Curriculum integrated in the Professional and Technological Education. It started from the following research problem: what are the implications of Emergency Remote Teaching - ERE in PTETML, considering technology, education and work? The general objective was to analyze the implications of emergency remote teaching (ERE), developed in the Technical Course of Medium Level in Informatics, in the Subsequent form, class 2021, IFAM- Campus Tabatinga-AM, through the categories technology, education and work. This is a qualitative, descriptive research using the case study method. The collection instruments were the questionnaire, the interview and the electronic survey. Data analysis consisted of creating a procedure for analyzing objective and subjective questions jointly, using Bardin's (1977) content analysis technique. 4 professors and 3 students from the subsequent computer science course, class 2021, participated in the research. The main results found showed the following notes: professors and students had difficulties during the ERE; the critical conception of work as an educational principle is not yet fully consolidated and; teacher training with regard to teaching and learning trends, mediated or not by digital technologies, needs to show a critical conception of education in EPT. The results and discussions also supported the preparation of the training guide “Methodologies and Educational Technologies: possible approaches for pedagogical practice in EPT”, which presents a totalizing perspective of work and its relations with education; and at the same time that it guides EPT professors regarding these two categories, it also exposes important elements to pedagogical practice, such as active methodologies and educational technologies.